Potentiality of banana (Musa) stem as raw material in chemical nonwood pulping / Leong Soo Kwan and Rakmi Abd Rahman - Leong, Soo Kwan; Abd Rahman, Rakmi (Institute of Research, Development and Commercialisation (IRDC), 2007)
Wood is not sufficient in many countries to meet the rise demand for paper and pulp. In recent years, a lot of researches have been done to find a new, nonwood raw material for paper production especially using agricultural waste. Agriculture industry is one of the main industries in Malaysia which has generated a large amount of waste every year such as banana stem, rice hull, sugarcane bagasse and wheat straw. These are regarded as abundant, inexpensive and readily available natural resources for pulping industry. The purpose of this paper is to study of the pulping potentialities of banana stems which are growing in Malaysia. In this research the banana stem is used as raw material in the pulping process for the purpose of producing cellulose as pulp. The chemical pulping method which is used in the study is soda pulping, where NaOH is the main chemical substance used in cooking and with anthroquinone as the additive. Temperature, residence time and dosage of chemical were the parameters to be manipulated in this non-wood chemical pulping process to get an optimum condition for pulping. A 3 litre batch reactor was used in this non-wood chemical pulping process. The concentration of NaOH used was varied from 10 – 45 % and cooking temperature was varied from 100 – 200 °C. The ratio of solid to liquid is set at 1:8 and also the cooking period was varied from 30 – 210 minutes. The result shows that the optimum yield of pulp from this study is at 20 % w/w NaOH, cooking at 160 °C with 120 minutes. The yield of pulp is around 30 %. The cellulose content in the pulp produced is as high as 90 %.